How to Connect Artisanal & Small-Scale Gold Miners in Uganda to the International Market for Ethically Produced ASM Gold? - Sturmes, David (Student Undergraduate Research E-journal!, 2018)
Four artisanal and small-scale mining organisations (ASMOs) producing gold in Uganda have been subjected to a value chain analysis, showing that they currently lack access to any legal market channels. Despite receiving high per gram prices for their gold on the illegal market, these organisations do not trust current trade partners regarding the measurements of weight and purity and end up making meagre profits due to high maintenance and production costs. Opportunities for an alternative route-to-market model have been explored in an effort to improve the producer community’s livelihood. The proposed system builds on; 1) an assurance and export mechanism utilizing blockchain traceability, 2) the provision of technical training and 3) on-the-spot payments. The most important aspect of making this system attractive to producer groups will be the provision of technical processing and mining equipment to boost efficiency, productivity and profitability. Through improved productivity and efficiency, ASMOs will benefit most from ethical sourcing ambitions.